Pernikahan Di Bawah Umur Dalam Perspektif Hukum Perkawinan - Fadhlullah Fadhlullah; Novi Andriani (Fakultas Hukum Universitas Muhammadiyah Aceh, 2018)
Underage marriages are marriages that are not in accordance with Law Number 1 of 1974 on Marriage. Article 7 paragraph (1) states